PENGARUH DESENTRALISASI TERHADAP HUBUNGAN ANTARA PARTISIPASI DALAM PENYUSUNAN ANGGARAN DAN KINERJA DINAS (Studi Kasus Pada Pemerintahan Kota Banjarbaru) - Jumirin Asyikin (EKUITAS (Jurnal Ekonomi dan Keuangan), 2005)
UU Number 22 and 25, 1999 about local government and financial balancing between central and local government, concerning about, the rule of decentralization and autonomy in making local budget for revenues and expenditure. Budgeting process is considered very important and concerned many different parties. Not only top managers but olso lower and middle manager play a vital role in making and evaluating some alternatives plan of the budgetr objectives. Budgeting always been used as the indicator of manager’s performance (Kren, 1992). Miah and Mia (1996), stated the empowerment and responsibility given from top to lower management level will biring about more cosequnecies of responsibility from lower manager toward the implementation of the decision that has been made. This research analysis the interaction and decentralization and the influence of participation in budgeting abd decentralization toward the performance of Dinas Pemerintah Kota Banjarbaru. The sample taken for this research is Dinas Pemerintah Kota Banjarbaru .Analysis unit used in this research are the chairman of government officer (kepala bagian), the chairman of division officer (kepala bagian) and the charmain of field officer (kepala bidang). From 56 questionaires that that have been sent, there 47 respondents have fullfillied, buat only 42 questionaires that are accepted and considered reliable to be analyzed in this research.Using simple in this research emprically this research result shows that participation in budgeting and decentralization signicantly influence the partisipation in budgeting and decentralization positive interaction between them. Meanwhile using multiple regression, empirically  the research result shows that budgeting and decentralization variables all together signicantly do not influence the performance of the governmental bureaus (Dinas Pemerintah Kota Banjarmasin).